Providing online social support to student writers: Virtual teaching strategies for positive engagement - Davis, Mary (Journal of Academic Writing, 2022)
One of the challenges for writing tutors during the pandemic has been trying to find ways to replicate on-campus contact and support for students. In response, this teaching practice-focused paper looks at ways to provide social support to students online with the aim of increasing engagement and enjoyment in the writing process. The paper is based on a workshop session given at the EATAW Conference, in which eight different strategies for engaging remote student writers were presented, discussed, and evaluated. These strategies are: establishing networks of peer support, providing a weekly social meeting, organising writing events, encouraging blog writing, helping students with planning and providing check-in points, helping with time management, sharing recommendations for other kinds of writing, and sharing recommendations for ways to enjoy writing. All of these strategies were developed by the author at a post-1992 teaching-focused university in the south of England during the pandemic. The paper examines the needs for these strategies and how academic writing tutors may use them in practice to engage remote writers, drawing on the conference workshop discussion. The paper concludes with some recommendations for EATAW to further support writing in remote contexts.